Desenvolvimento e avaliação de um programa de ensino de pré-requisitos de leitura e escrita para pré-leitores - Rezende, Mariana de (2022)
The search for an efficient literacy method is not new. An approach that has been proving effective in educational environments is Behavior Analysis. This approach has supported interventions with the purpose of remedying the gaps in teaching methods of reading and writing skills regularly used in schools. The present study developed and evaluated a programmed teaching module aimed to teach discriminative skills considered to be elementary for learning to read and write. In order to do this, the present work was divided into two stages: 1) planning and programming a Preparatory Module for teaching elementary reading skills as well as its transposition into computer language and its indexing to the GEIC; 2) implementation and evaluation of three participants of the first full version of the Preparatory Module. Three children from two Brazilian states participated, aged between 9 and 10 years old, enrolled in the 2nd and 3rd grade of elementary school. The teaching program consisted of nine teaching tasks and four probes distributed in four teaching units. Trial blocks with difficulty progression were programmed with accuracy criterion in order to assure the learning of the target abilities. Among the participants, there was performance variability when running the probes; deterioration of some skills after the teaching steps; high number of repetitions of the teaching steps (i.e., due to not meeting the criteria in the first exposure) and difficulties in identifying possible intervening variables that may have affected performance (i.e., changes in the application of the teaching program by the research assistant). The extension of the teaching program, and the remote application condition of the program, assisted by a research assistant, were considered probable problems in application. The results of the present study are promising and indicate the potential of the Preparatory Module to reach the criterion of effectiveness in order to be able to make part of the ALEPP Program.